Konsep Dakwah 'Â'idh Al-Qornî Dalam Pembinaan Pemuda Islam - Urfiyanti, Ana, Dr. M. Muinudinillah Basri, M.A, Dr. Syamsul Hidayat, M.Ag (2015)
Doctrine sky ( Islam ) has been grounded through the angel Gabriel to the Prophet Muhammad and the holy book the Qur'an as a source of guidance , guidance and strength for the Muslims all over the world . Through the Qur'an and the Sunnah of the Prophet of Islam is this guide humanity to follow the guidance of Allah and the Messenger , by carrying out propaganda commanding the good and evil nahyi . Not a few hadiths of the Prophet Muhammad that contains the values of propaganda that we need to apply today . Among the sayings of the Prophet Muhammad is commanded to his community to ma'ruf nahi . Diman commanding the good and forbidding the evil is missionary activity that requires a concept in order to achieve what the goals and objectives in the propaganda . concept presented propaganda ' Â'idh al - Qornî very weighty and very relevant and substantial effect on the youth of Islam . Da'wah delivered by ' Â'idh al - Qornî either through oral or written media is a propaganda concept containing noble values , because an appeal to the moral commendable , a beautiful string of words , softens the heart and feelings , called melaksanakn religion , laden with values virtue , and pay attention to ethics . Da'wah ' Â'idh al - Islam Qornî in fostering youth apiknya drafted in such a way , so as to give birth to young men who were thinking positive and mature . Thus the Muslim youth are able and ready to be agents of change that will continue the propaganda struggle relay Muhammad SAW . concept of propaganda ' Â'idh al - Qornî served with a variety of styles and expressions as well as the method of describing a preacher who tried to persuade the youth to light torches propaganda fighting spirit in the face of this earth with intention and attention, so invite enthusiastic high from youth to explore the propagation of Islam in kaafah. Hence, the authors wanted to analyze " The concept of Da'wah ' Â'idh Al - Qornî in fostering Islamic youth " Because of that I know he is a senior figure in handling the issue of youth and this has been stated by many seniors propaganda , scholars ' and fuqoha ' this century . The research method I use is descriptive analytical method , the research library (library research ) , in this study only described some concepts propaganda ' Â'idh Al - Qornî implicit in his books later writers megkomperasikan analysis with other concepts . While research in this thesis is still a depiction ansih globally , so it still requires in-depth and detailed assessment on his concept of this , in order to produce a product that is new science that is capable of enlightenment for the Muslims in fostering Islamic youth .